Simultaneous occurrence of tropical cyclones on either side of the equator in the Indian Ocean area - MUKRERJEE , A. K.; PADMANABHAM, K. P. (MAUSAM, 1977)
Malurkar (1950) postulated the formation of depressions or cyclones on both Sides of equator within a narrow ( <=40°) longitudinal belt, Pisharoty and Kulkarni (1956) conducted some case studies and Came to the conclusion that they do form as postulated by Malurkar and there is mutual interaction with one another so much so that when one system Intensifies the other weakens, Kuettner (1967) opined that the existence and, alignment of hills in Sumatra are responsible for simultaneous occurrences of storms and depressions on both sides of equator, To verify the above conclusions the present study was undertaken, It covers an 11 year period from 1964 to 1974. During the period as many as 14 storms/depressions formed on both sides of equator. Of course, there were some years when such systems did not develop, They form in transition months with a bias towards the post monsoon season, Kuettner’s conclusions are generally supported. Pisharoty and Kulkarni’s conclusions could not be supported, by the present study, Malurkar’s conclusion that two tropical storms cannot both continue to move westwards and co-exist on either side of the equator when the longitudinal separation is small (<=10°) is also supported.